Sebaceous hyperplasia: systemic treatment with isotretinoin - Sandra Tagliolatto; Octavio de Oliveira Santos Neto; Maurício Mota de Avelar Alchorne; Mauro Yoshiaki Enokihara (Sociedade Brasileira de Dermatologia, 2015)
The study aimed to verify the therapeutic action of isotretinoin in the treatment of sebaceous hyperplasia. During two months, 20 patients with sebaceous hyperplasia took isotretinoin at a dosage of 1mg/kg per day. Their skin lesions were counted and photographed before and after treatment and re-evaluated two years later. The average number of sebaceous hyperplasia lesions before treatment was 24 per patient. At the end of two months of therapy, the number of lesions decreased to 2 per patient. The statistically analyzed data showed a reduction in the number of lesions following isotretinoin use (p < 0.05). Two years after the end of the treatment, the average number of sebaceous hyperplasia lesions was 4 per patient. There were no severe side effects. Thus, the data analysis suggests that isotretinoin is a safe and effective drug for treating the disease under study.